Ultra-Wideband Five-Tier LM-mode Filters Optimized with knowledge-based CAD system - Yushchenko, A. G.; Mamedov, D. B. (НТУ "ХПІ", 2013)
An original knowledge-based CAD system for step-by-step automated development offive-tier filters base don wave guide-dielectric resonators with the lowest LM-modes has been proposed. The basic idea of the system created consists in physical analysis of signals passing through the filter, which is performed on the basis of a known solution for electrodynamic problem of scattering of fundamental electromagnetic waves in a multi-tier structure. Regularities in formation of the filter ultra-wide bandwidths and formalized them in the form of production rules for the system were discovered. A comparative analysis of frequency responses for three- and five-tier UWB filters, optimized with the system has been also provided. The designed filters are intended for the next generation of millimeter waveband wireless systems and conform to the latest standards like ECMA-387, WirelessHD, IEEE 802.15.3c and IEEE 802.11ad.

Предложена оригинальная САПР последовательного проектирования пятизвенных фильтров на основе волноводно-диэлектрических резонаторов с низшими LM-модами. Ключевая идея разработанной системы заключается в физическом анализе сигнала прошедшего через фильтр, который рассчитывается на основе известного решения электродинамической задачи рассеяния основной волны на многозвенной структуре. Установлены закономерности формирования ультрашироких полос пропускания фильтров, которые формализованы в виде логических продукций. Проведен сравнительный анализ АЧХ трех- и пятизвенных ультрашироких фильтров, сконструированных системой. Параметры фильтров отвечают новому поколению радиотелекоммуникационных систем миллиметрового диапазона соответствующих новейшим стандартам ECMA-387, WirelessHD, IEEE 802.15.3candIEEE 802.11ad.
Keywords: Ultra-widebandfive-tier filters; Knowledge-based CAD system; WirelessHD; IEEE 802.15.3c; IEEE 802.11ad